2022
DOI: 10.1007/s11356-022-20644-w
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study on dioxins and dioxin-like polychlorinated biphenyls in milk and dairy products from the Latium region (Italy) over a 7-year study period (2011–2017)

Abstract: This study reports the data of polychlorinated dibenzo-p-dioxins (PCDDs), -furans (PCDFs), and polychlorinated biphenyls dioxin-like (dl PCBs) measured in a total of 260 samples of the dairy supply chain collected over a period of 7 years (2011–2017) in the Latium region (Italy). Levels and average profiles of congeners were reported for each group of the analyzed dairy matrices, and any differences between different sampling strategies were considered (around likely pollutant sources or casual sampling). Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…OCDD and 1,2,3,4,6,7,8-HpCDD are polychlorinated dibenzo-p-dioxins (PCDDs) as well as the dominant PCDD/F congener [ 31 , 32 ]. Battisti Sabrina et al [ 33 ] found that OCDD was the most abundant PCDD/F congener in dairy products collected in the Latium region of Italy (2011–2017). L. P. Fang et al [ 34 ] found that fish tissues contained a relatively large amount of OCDD, accounting for 54% of the total PCDD/F congeners.…”
Section: Discussionmentioning
confidence: 99%
“…OCDD and 1,2,3,4,6,7,8-HpCDD are polychlorinated dibenzo-p-dioxins (PCDDs) as well as the dominant PCDD/F congener [ 31 , 32 ]. Battisti Sabrina et al [ 33 ] found that OCDD was the most abundant PCDD/F congener in dairy products collected in the Latium region of Italy (2011–2017). L. P. Fang et al [ 34 ] found that fish tissues contained a relatively large amount of OCDD, accounting for 54% of the total PCDD/F congeners.…”
Section: Discussionmentioning
confidence: 99%